USING ANCHOR CHART MEDIA TO INCREASE THE READING COMPREHENSION OF THE TENTH GRADERS OF SMA NEGERI 1 KOTA MUNGKID IN THE ACADEMIC YEAR 2017/2018 - Adi Hermawan (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2018)
Reading is one of the receptive skills. The goal of reading skill is comprehension. Unfortunately, the tenth graders of SMA N 1 Kota Mungkid in the academic year 2017/2018 still got difficulty in comprehending written text. This condition happened because the students have low motivation and the variation of the teaching media. There are two objectives of this research. First, it is to know how great can the use of Anchor Chart Media increase the learning motivation of narrative text reading comprehension of the tenth graders of SMA Negeri 1 Kota Mungkid in the academic year 2017/2018. Second, it is to know how great the improvement of the narrative text reading comprehension of the tenth graders students of SMA N 1 Kota Mungkid in the academic year 2017/2018 who are taught by using anchor chart media.The writer collected the data by using classroom action research. The subject of the research was the class of X IPA 2 of SMA Negeri 1 Kota Mungkid in the academic year 2017/2018. The writer finds that the use of Anchor Chart Media can increase the student’s learning motivation. The observation and questionnaire results indicate the students have high motivation in English learning process. Based on the above results, the writer concludes that the use of Anchor Chart Media can increase the learning motivation narrative text reading comprehension of the tenth graders of SMA Negeri 1 Kota Mungkid in the academic year 2017/2018. The writer suggests both the teachers and the students to use Anchor Chart Media as an alternative in teaching and learning.